Regulation innovation - Barefoot, Jo Ann (Henry Stewart Talks, 2018)
Regtech, Regulation-related activities, Regtech for regulators and for compliance, The growth of RegTech, RegTech NGOs, International initiatives, Engaging with the New Technology, Technology Trends, The future of RegTech, Using data for fairness, The political framework